PN junction material carrier concentration and mobility test method and application
By combining Hall test, ion implantation, corrosion to form inclined surfaces and IV curves to determine the junction depth, the P-type carrier concentration and mobility of PN junction materials are accurately measured, and the cumbersome and inaccurate tests in the prior art are solved. The problem has achieved efficient and accurate test results.
Patent Information
- Application Number
- CN202411470267.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-10-21
AI Technical Summary
The methods for testing carrier concentration and mobility of PN junction materials in the prior art are cumbersome and inaccurate, and cannot effectively solve the testing problems of bipolar carrier materials, resulting in a decrease in yield and waste of manpower and material resources.
A test method including Hall test, ion implantation, corrosion forming inclined surface and IV curve to determine the junction depth is adopted. The P-type carrier concentration and mobility of the PN junction material are calculated through formulas to improve the testing accuracy and simplicity.
Accurate measurement of carrier concentration and mobility of PN junction material is achieved, the testing process is simplified, error is reduced, the problems of cumbersome and inaccurate testing in the existing technology are solved, and the yield and resource utilization efficiency are improved.
Smart Images

Figure CN119492968A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of semiconductors, and in particular to a method and application for testing carrier concentration and mobility of PN junction materials. Background Art
[0002] PN junction is a material in which holes and electrons jointly participate in conduction and has complex electrical transport characteristics. Especially after injection into the junction, the electrical transport behavior cannot be tested and characterized by a single method. Therefore, a reasonable and scientific method is needed to test and model the PN junction device.
[0003] In the prior art, the Hall effect is often used to characterize the transport characteristics of PN junctions. The carrier type is determined and the concentration is calculated based on the size and positive and negative of the Hall coefficient. However, a PN junction containing bipolar carriers (such as HgCdTe after the junction) has both holes and electrons as carriers, and its carrier type and concentration cannot be simply determined by the Hall effect. The effective mass of holes in HgCdTe materials is more than 30 times that of electrons, and the mobility is much smaller than that of electrons, with a difference of up to two orders of magnitude. Therefore, good P-type HgCdTe is often mistaken for weak N-type in Hall tests and cannot be taped out, resulting in huge waste.
[0004] The existing technology also commonly uses the stripping Hall method to test the bipolar carrier concentration of the PN junction containing bipolar carriers. The entire sample is completely immersed in the etching solution, the corrosion thickness is measured by a Fourier infrared spectrometer, and the carrier test is performed using a Hall test system. It is usually necessary to repeat the etching more than 6 times, and finally the carrier concentration of each stripped material is obtained by fitting. The entire process of the stripping Hall method is too cumbersome, and it often takes half a day for one device, which is extremely wasteful of manpower. At the same time, the accuracy of layer-by-layer corrosion combined with Fourier testing is limited, and the error is greater than 0.3μm. It is impossible to obtain the accurate thickness of the P-type layer, resulting in large errors in the calculation of carrier concentration and mobility.
[0005] Therefore, in order to address the problems of complicated testing methods and inaccurate results in the prior art, a method for testing the carrier concentration and mobility of PN junction materials with a simple method and small error is urgently needed. Summary of the invention
[0006] The present invention provides a method and application for testing the carrier concentration and mobility of a PN junction material to solve the problems of cumbersome testing methods and inaccurate test results in the prior art. The method for testing the carrier concentration and mobility of a PN junction material of the present invention can obtain the bipolar carrier concentration and mobility of electrons and holes, and the testing method is simple and has a small error, which can effectively solve the problems of inaccurate carrier measurement and inability to measure the P-type concentration in the prior art, as well as the problems of cumbersome testing process, reduced yield, and waste of manpower and material resources.
[0007] The first object of the present invention is to provide a method for testing carrier concentration and mobility of a PN junction material, comprising:
[0008] S1. Perform Hall test on N-type substrate to obtain carrier concentration n and mobility μ of N-type substrate. n ;
[0009] S2. P-type ions are doped on the N-type substrate by ion implantation to form a P-on-N structure sample, and the P-on-N structure sample is subjected to a Hall test to measure the Hall coefficient R of the P-on-N structure sample. h , resistivity ρ;
[0010] S3, the P-on-N structure sample obtained in step S2 is corroded by the corrosive solution to form an inclined surface, and the corrosion depth h is measured;
[0011] S4. Use the IV curve to determine the junction depth and obtain the thickness d of the P layer of the P-on-N structure. p With the thickness of N-type layer d n ;
[0012] P-type carrier concentration p and mobility μ of PN junction material p The calculation formulas are shown in the following formula (1) and formula (2):
[0013]
[0014] Among them, d in the above formula (1) and formula (2) p is the thickness of the P layer, d n is the thickness of the N-type layer, q is the electron charge, n is the carrier concentration of the N-type substrate, μ n is the mobility of the N-type substrate, R h is the Hall coefficient of the P-on-N structure sample, and ρ is the resistivity.
[0015] The test method of the present invention uses an IV curve to determine the junction depth. Compared with the capacitance-voltage method, the top electrode of the passivation layer and the bottom electrode of mercury cadmium telluride are extracted, the voltage is swept to measure the capacitance, and the carrier concentration, mobility and junction depth are measured through fitting calculation. The test results of the capacitance-voltage method will be affected by the electron concentration of the passivation layer, and cannot directly reflect the carrier concentration of the PN junction, and the electrode extraction process is more difficult. The PN junction depth position is confirmed by the IV curve, and then the specific junction depth is measured by the step profiler.
[0016] The mobility spectroscopy method directly measures the Hall effect of the sample, and combined with fitting, it can measure the carrier concentration of the multi-carrier system. However, peak spectra that are unrelated to the PN junction often appear in the calculation process, that is, the carrier concentration has no actual physical meaning, and the junction depth data cannot be obtained.
[0017] The stripping Hall measurement method uses layer-by-layer corrosion, layer-by-layer measurement, and layer-by-layer fitting to obtain the carrier concentration mobility and corresponding junction depth of the sample at different depths. However, the process is extremely cumbersome, and the calculation accuracy is greatly affected by corrosion and Fourier transform infrared spectrometer testing. The data obtained is of low accuracy, especially the junction depth position cannot be accurately confirmed.
[0018] In contrast, the IV curve used in the present invention determines the junction depth and can calculate the junction depth more accurately. When the thickness of the N-type layer and the P-on-N mixed carrier concentration and mobility are known, an inclined surface with a depth of 0.01-10μm is formed by etching means, and a PN junction device is formed by micro-nano processing to lead out an IV test electrode. The junction depth is confirmed based on the IV curve changing from a resistance characteristic to a diode. Combined with the above-mentioned junction depth, the N-type layer and the P-on-N mixed carrier concentration and mobility, the formula can be used to calculate the carrier concentration and mobility of the P-type layer formed by injection. The test accuracy is improved, and the steps of the inclined surface can be seen, and the inclined surface can also be regarded as an inclined table.
[0019] According to a preferred embodiment of the present invention, the N-type substrate is any one of mercury cadmium telluride, vanadium oxide, indium gallium arsenide, and indium antimonide; preferably mercury cadmium telluride;
[0020] And / or, the P-type ion is any one of As ion, Cu ion, Ag ion and Au ion; preferably As ion;
[0021] Preferably, the N-type substrate has a thickness of 1-100 μm, preferably 1-50 μm, more preferably 2-10 μm, and further preferably 3-9 μm; a length of 0.1-100 mm, preferably 10-50 mm; a width of 0.1-100 mm, preferably 10-50 mm;
[0022] Preferably, the energy of the As ion implantation is 60-500 KeV, preferably 100-180 KeV; the dose is 10 11 ~10 16 / cm 2 .
[0023] According to a preferred embodiment of the present invention, the step of forming an inclined surface (or inclined table) in step S3 includes, after applying photoresist on the edge of the P-on-N structure sample, immersing it in a 0.1-30wt% bromine methanol etching solution, immersing it downward by 0.01-5mm every 0.1-10s until the inclined surface is formed, removing the etching solution and photoresist on the surface, preferably using methanol and / or acetone to clean and remove the etching solution and photoresist on the sample surface.
[0024] According to a preferred embodiment of the present invention, before measuring the IV curve in step S4, the P-on-N structure sample is further subjected to patterning treatment.
[0025] According to a preferred embodiment of the present invention, in step S1, the Hall test is performed in a Hall test system, and the Hall coefficient R of the material is measured by the Van der Pauw method. h , resistivity ρ; preferably, the Hall test is performed under the action of a first magnetic field perpendicular to the N-type substrate, a first current passes through the N-type substrate, and a first Hall voltage V is measured y1 The Hall test system calculates the N-type carrier concentration n and mobility μ n More preferably, the magnetic field strength of the first magnetic field is 0-10T, and the current strength of the first current is I x1 0-10mA.
[0026] According to a preferred embodiment of the present invention, in step S2, the P-on-N structure sample is pressed with an indium lead electrode and connected to a Hall test system for a Hall test; preferably, in the Hall test, under the action of a second magnetic field perpendicular to the P-on-N structure sample, a second current passes through the P-on-N structure sample, and a second Hall voltage V is measured. y2 The Hall coefficient R of the P-on-N structure sample is calculated by the Hall test system. h More preferably, the magnetic field strength of the second magnetic field is 0-10T, and the current strength of the second current is I x2 0-10mA.
[0027] According to a preferred embodiment of the present invention, in step S4, the P-on-N structure sample after etching in step S3 is subjected to resist coating, photolithography development, and then etching treatment, and an IV curve corresponding to the P-on-N structure sample is measured using a semiconductor parameter tester; preferably, the etching depth is 0.01-10 μm; and / or, the IV curve corresponding to the junction depth changes from a resistance characteristic to a diode characteristic.
[0028] According to a preferred embodiment of the present invention, the measuring instrument for step measurement is a step profiler;
[0029] And / or, the gluing apparatus is a gluing machine;
[0030] And / or, the photolithography and development instrument is a photolithography machine;
[0031] And / or, the etching is ICP etching;
[0032] And / or, the semiconductor parameter tester is a Keithley 4200 semiconductor parameter tester.
[0033] The second objective of the present invention is to provide an application of the testing method of the PN junction material in the field of infrared detectors.
[0034] The beneficial effects of the present invention are as follows: by using the present invention to measure and fit the material parameters of a PN junction device, the measurement accuracy of the junction depth reaches 0.05 μm, the difficulty of testing P-type carriers is solved, and a relatively accurate carrier concentration mobility can be obtained.
[0035] It has a guiding role in the process of low-noise, low lateral diffusion and low leakage infrared detectors, can improve the detector design and development capabilities, optimize the carrier concentration and mobility of the material, reduce the dark current of the device, and improve the performance of the focal plane components. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a schematic diagram of the process of the PN junction material testing method of this application. DETAILED DESCRIPTION
[0037] The present invention will be further described below in conjunction with specific embodiments, but they do not constitute any limitation to the present invention.
[0038] In the following embodiments, the N-type substrate is made of mercury cadmium telluride material; the size of the N-type substrate is 20*20 mm and the thickness is 8 μm;
[0039] P-type ions are As ions;
[0040] The measuring instrument for step measurement is a step meter;
[0041] The instrument for applying glue is a glue coating machine;
[0042] The instrument for photolithography and development is a photolithography machine;
[0043] The etching is ICP etching;
[0044] The semiconductor parameter tester is Keithley 4200 semiconductor parameter tester.
[0045] Figure 1 In this patent, junction formation and metallization are common terms in the industry. Junction formation in this patent can be understood as referring to the formation of a PN junction by ion implantation, and metallization is the growth of a metal film layer to lead out a test electrode.
[0046] [Example 1]
[0047] like Figure 1 As shown, the test method for carrier concentration and mobility of PN junction material of the present invention comprises the following steps:
[0048] S1. Select the HgCdTe sample as the N-type substrate, use the indium pressure to lead out the Hall test electrode to connect the Hall test system, add liquid nitrogen to cool down to 77K, the first magnetic field is ±1T, and the first transverse current I is passed. x =1mA, measure the first longitudinal Hall voltage V y1 The Hall test system is based on the size, thickness and first Hall voltage V of the N-type substrate.y1 , the carrier concentration of N-type substrate can be directly measured as n = 9 × 10 14 / cm 3 and mobility μ n =10500cm 2 / V·s;
[0049] S2, As ions with energy of 150KeV are implanted into the HgCdTe sample to form a P-on-N structure sample. The P-on-N structure sample uses pressed indium to lead out the Hall test electrode, connects to the Hall test system, adds liquid nitrogen to cool down to 77K, the second magnetic field is ±1T, and the transverse second current I is passed. x =1mA, measure the longitudinal second Hall voltage V y2 The Hall test system is based on the size, thickness and second Hall voltage V of the P-on-N structure sample. y2 The Hall coefficient R of the P-on-N structure sample can be directly measured h =3.035cm 3 / C and resistivity ρ = 0.35Ω·cm.
[0050] S3. Coat the edge of the HgCdTe sample with photoresist for protection, immerse it in 0.5% bromomethanol etching solution in the vertical direction (the HgCdTe sample is perpendicular to the solution surface), immerse it downward by 1 mm every 5 seconds, and etch it for a total of 100 seconds. After forming an inclined table, place it in methanol solution for 3 minutes and acetone solution for 5 minutes. Remove bromomethanol and photoresist, and use a step meter to measure the edge steps to determine the corrosion depth h.
[0051] S4. Use photolithography and etching to pattern the HgCdTe sample to obtain PN junctions of different depths. Place it in a low temperature environment and measure the IV curve to determine the junction depth and obtain the P layer thickness d. p With the thickness of N-type layer d n The junction depth is determined by measuring the IV curve of the inclined table surface. The inclined table surface is formed by corrosion, half of which has PN junction characteristics and the other part is an N-type layer. The critical thickness of the IV curve that can be detected is the junction depth.
[0052] The P-on-N sample was placed in a coating machine with a rotation speed of 6000r / min. After exposure and development by a photolithography machine, ICP etching was used with an etching depth of 0.5μm to form a PN junction device. The IV curve was measured using a Keithley 4200 semiconductor parameter tester. When the IV curve changes from a resistance characteristic to a diode characteristic, the corresponding corrosion depth h is the junction depth, and the measurement accuracy can reach 0.05μm, which is the thickness of the P-type layer d p = 1.35 μm, total thickness 8 μm minus d p That is the thickness of the N-type layer d n =6.65μm.
[0053] In the following formula (1) and formula (2), dp is the thickness of the P layer, d n is the thickness of the N-type layer, q is the electron charge, n is the carrier concentration of the N-type substrate, μ n is the mobility of the N-type substrate, R h is the Hall coefficient of the P-on-N structure sample, and ρ is the resistivity.
[0054] According to formula (1) and formula (2), the n and μ are measured. n , R h d p d n , ρ are fitted, the P-type carrier concentration p and mobility μ of the PN junction material p Calculation formula.
[0055]
[0056] The calculation shows that the P-type carrier concentration p = 2.3 × 10 18 / cm 3 , mobility μ p =650cm 2 / V·s.
[0057] The thickness is measured by calculating the infrared transmission spectrum and combining the above formula (1) and formula (2) to obtain the thickness. However, the surface of mercury cadmium telluride is rough and the measurement error of the transmission spectrum is 0.05 microns.
[0058] [Example 2]
[0059] The method for testing carrier concentration and mobility of PN junction materials of the present invention comprises the following steps:
[0060] S1. Select the HgCdTe sample as the N-type substrate, use the indium pressure to lead out the Hall test electrode to connect the Hall test system, add liquid nitrogen to cool down to 77K, the first magnetic field is ±1T, and the first transverse current I is passed. x =1mA, measure the first longitudinal Hall voltage V y1 The Hall test system is based on the size, thickness and first Hall voltage V of the N-type substrate. y1 , the carrier concentration of N-type substrate can be directly measured as n = 9 × 10 14 / cm 3 and mobility μ n =10500cm 2 / V·s;
[0061] S2, As ions with energy of 300KeV are implanted into the HgCdTe sample to form a P-on-N structure sample. The P-on-N structure sample uses pressed indium to lead out the Hall test electrode, connects to the Hall test system, adds liquid nitrogen to cool down to 77K, the second magnetic field is ±1T, and the transverse second current I is passedx =1mA, measure the longitudinal second Hall voltage V y2 The Hall test system is based on the size, thickness and second Hall voltage V of the P-on-N structure sample. y2 The Hall coefficient R of the P-on-N structure sample can be directly measured h =2.035cm 3 / C and resistivity ρ = 0.5Ω·cm.
[0062] S3. Coat the edge of the mercury cadmium telluride sample with photoresist for protection, immerse it in 0.5% bromine methanol etching solution in the vertical direction, immerse it downward by 1mm every 5 seconds, and etch it for a total of 100 seconds. After forming an inclined table, put it in methanol solution for 3 minutes and acetone solution for 5 minutes. Remove bromine methanol and photoresist, and use a step meter to measure the edge steps to determine the corrosion depth h at different times, where the corrosion thickness in 100 seconds is 2.7μm.
[0063] S4. Use photolithography and etching to pattern the HgCdTe sample to obtain PN junctions of different depths. Place it in a low temperature environment and measure the IV curve to determine the junction depth and obtain the P layer thickness d. p With the thickness of N-type layer d n .
[0064] The junction depth is determined by measuring the IV curve of the inclined table surface. The inclined table surface is formed by corrosion, half of which has PN junction characteristics and the other part is an N-type layer. The critical thickness of the IV curve that can be detected is the junction depth.
[0065] The IV curve confirms the location of the PN junction depth, and then the specific junction depth is measured by a step profiler.
[0066] The P-on-N sample was placed in a coating machine with a rotation speed of 6000r / min. After exposure and development by a photolithography machine, ICP etching was used with an etching depth of 0.5μm to form a PN junction device. The IV curve was measured using a Keithley 4200 semiconductor parameter tester. When the IV curve changes from a resistance characteristic to a diode characteristic, the corresponding corrosion depth h is the junction depth, and the measurement accuracy can reach 0.05μm, which is the thickness of the P-type layer d p = 2.1 μm, total thickness 8 μm minus d p That is the thickness of the N-type layer d n =5.9μm.
[0067] According to formula (1) and formula (2), the n and μ are measured. n , R h d p d n , ρ are fitted, the P-type carrier concentration p and mobility μ of the PN junction material p Calculation formula.
[0068]
[0069] The calculation shows that the P-type carrier concentration p = 2.3 × 10 18 / cm 3 , mobility μ p =780cm 2 / V·s. The thickness error is also 0.05μm.
[0070] [Comparative Example 1]
[0071] The peeling Hall method is used to test the carrier concentration and mobility. The method steps are as follows:
[0072] S1. As ions with energy of 150 KeV are implanted into the HgCdTe sample to form a P-on-N structure sample. The P-on-N structure sample uses pressed indium to lead out the Hall test electrode, connects to the Hall test system, adds liquid nitrogen to cool down to 77K, the second magnetic field is ±1T, and the transverse second current I is passed. x =1mA, measure the longitudinal second Hall voltage V y2 The Hall test system is based on the size, thickness and second Hall voltage V of the P-on-N structure sample. y2 The Hall coefficient R of the P-on-N structure sample can be directly measured h =3.035cm 3 / C and resistivity ρ = 0.35Ω·cm.
[0073] S2. The HgCdTe sample was immersed in 0.5% bromine methanol etching solution for 15 seconds, then placed in methanol solution for 3 minutes and acetone solution for 5 minutes to remove bromine methanol and photoresist. The etching rate was the same as that in Example 1, so the etching depth h1=0.41 μm was obtained.
[0074] S3, the sample is corroded once, and the Hall test electrode is drawn out by pressing indium. It is connected to the Hall test system, and liquid nitrogen is added to cool it down to 77K. The second magnetic field is ±1T, and the second transverse current I is passed. x =1mA, measure the longitudinal second Hall voltage V y2 The Hall test system is based on the size, thickness and second Hall voltage V of the P-on-N structure sample. y2 The Hall coefficient R of the P-on-N structure sample can be directly measured h =3.335cm 3 / C and resistivity ρ = 0.41Ω·cm.
[0075] S4, repeat steps S2 and S3, repeat the etching and Hall test many times until the carrier type is N-type, the etching thickness is 0.35μm, 0.45μm, 0.43μm, 0.34μm, 0.36μm respectively, and the thickness of the P-type layer is 2.34μm. The Hall coefficient and resistivity of each layer are calculated to obtain the carrier mobility and concentration of each layer. The average value is taken, and the P-type carrier concentration is 3.2±10 18 / cm 3 , the mobility is 730cm 2 / V·s.
[0076]
[0077] Since it is impossible to achieve continuous changes in the corrosion thickness and the corrosion rate is not uniform each time, the thickness error of the P-type layer is more than 0.3μm (determined by the stripping Hall test method, usually the corrosion depth exceeds 0.3μm each time, so it is impossible to obtain the carrier concentration change data within the 0.3μm range).
[0078] Any numerical value mentioned in the present invention includes all values increasing by one unit each time from the lowest value to the highest value if there is only an interval of two units between any minimum value and any maximum value. For example, if the amount of a component is declared, or such as the thickness of an N-type substrate is 1-100 μm, in this specification it means that 2-99, 3-98... and 49-52 and 50-51 are specifically listed. For non-integer values, 0.1, 0.01, 0.001 or 0.0001 can be appropriately considered as a unit. These are just some specially specified examples. In this application, in a similar manner, all possible combinations of numerical values between the listed lowest value and the highest value are considered to have been disclosed.
[0079] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.
Claims
1. A method for testing carrier concentration and mobility of PN junction materials, characterized in that: include: S1. Perform Hall test on N-type substrate to obtain carrier concentration n and mobility μ of N-type substrate. n ; S2. P-type ions are doped on the N-type substrate by ion implantation to form a P-on-N structure sample, and the P-on-N structure sample is subjected to a Hall test to measure the Hall coefficient R of the P-on-N structure sample. h , resistivity ρ; S3, corroding the P-on-N structure sample obtained in step S2 with a corrosive solution to form an inclined surface, and measuring the corrosion depth h; S4. Use the IV curve to determine the junction depth and obtain the thickness d of the P layer of the P-on-N structure. p With the thickness of N-type layer d n ; P-type carrier concentration p and mobility μ of PN junction material p The calculation formulas are shown in the following formula (1) and formula (2): Among them, d in the above formula (1) and formula (2) p is the thickness of the P layer, d n is the thickness of the N-type layer, q is the electron charge, n is the carrier concentration of the N-type substrate, μ n is the mobility of the N-type substrate, R h is the Hall coefficient of the P-on-N structure sample, and ρ is the resistivity.
2. The testing method according to claim 1, characterized in that: The N-type substrate includes any one of mercury cadmium telluride, vanadium oxide, indium gallium arsenide and indium antimonide; preferably mercury cadmium telluride; And / or, the P-type ions include any one of As ions, Cu ions, Ag ions and Au ions; preferably As ions; Preferably, the N-type substrate has a thickness of 1-100 μm, preferably 1-50 μm, more preferably 2-10 μm, and further preferably 3-9 μm; a length of 0.1-100 mm, preferably 10-50 mm; a width of 0.1-100 mm, preferably 10-50 mm; Preferably, the energy of the P-type ion implantation is 60-500 KeV, preferably 100-180 KeV; the dose is 10 11 ~10 16 / cm 2 .
3. The testing method according to claim 1 or 2, characterized in that: Step S3 of forming an inclined surface comprises: after applying photoresist on the edge of the P-on-N structure sample, immersing it in a bromomethanol etching solution, immersing it downward by 0.01-5mm every 0.1-10s until the inclined surface is formed, removing the etching solution and photoresist on the surface, preferably using methanol and / or acetone to clean and remove the etching solution and photoresist on the surface of the sample; preferably, the concentration of the bromomethanol etching solution is 0.1-30wt%.
4. The testing method according to claim 1 or 2, characterized in that: Before measuring the IV curve in step S4, the P-on-N structure sample is further subjected to patterning.
5. The testing method according to claim 1 or 2, characterized in that: In step S1, the Hall test is performed in the Hall test system, and the Hall coefficient R of the material is measured by the Van der Pauw method. h , resistivity ρ; preferably, the Hall test is performed under the action of a first magnetic field perpendicular to the N-type substrate, a first current passes through the N-type substrate, and a first Hall voltage V is measured y1 The Hall test system calculates the N-type carrier concentration n and mobility μ n More preferably, the magnetic field strength of the first magnetic field is 0-10T, and the current strength of the first current is I x1 0-10mA.
6. The testing method according to claim 1 or 2, characterized in that: In step S2, the P-on-N structure sample is pressed with an indium lead electrode and connected to a Hall test system for a Hall test; preferably, in the Hall test, a second current passes through the P-on-N structure sample under the action of a second magnetic field perpendicular to the P-on-N structure sample, and a second Hall voltage V is measured. y2 The Hall coefficient R of the P-on-N structure sample is calculated by the Hall test system. h More preferably, the magnetic field strength of the second magnetic field is 0-10T, and the current strength of the second current is I x2 0-10mA.
7. The testing method according to claim 1 or 2, characterized in that: In step S4, the P-on-N structure sample after etching in step S3 is subjected to resist coating, photolithography development, and etching treatment, and the IV curve corresponding to the P-on-N structure sample is measured using a semiconductor parameter tester.
8. The testing method according to claim 7, characterized in that: The etching depth is 0.01-10 μm; and / or, the junction depth corresponds to the IV curve changing from a resistance characteristic to a diode characteristic.
9. The testing method according to claim 7, characterized in that: The measuring instrument for testing the corrosion depth h of the inclined surface is a step profiler; And / or, the gluing apparatus is a gluing machine; And / or, the photolithography and development instrument is a photolithography machine; And / or, the etching is ICP etching; And / or, the semiconductor parameter tester is a Keithley 4200 semiconductor parameter tester.
10. Application of the test method for carrier concentration and mobility of PN junction materials according to any one of claims 1 to 9 in the field of infrared detectors.
Citation Information
Patent Citations
Method for measuring electric parameter of gallium arsenide pseudomorphic HEMT (high electron mobility transistor) material
CN102313835A
Method of testing HgCdTe pn junction material
CN109116270A
Method for measuring and calculating doping concentration of highly-doped semiconductor
CN111024745A
Evaluation method for tellurium-cadmium-mercury doping activation rate
CN116482150A
A novel method for measuring current carrier mobility of magnetic semiconductor
CN1971295A
Cited By
Detection method for current carrier concentration of antimonide material
CN121275854A